2021
DOI: 10.1093/ofid/ofab254
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bamlanivimab Monoclonal Antibody Treatment on Hospitalization and Mortality Among Nonhospitalized Adults With Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: Background Monoclonal antibody treatment may prevent complications of COVID-19. We sought to quantify the impact of bamlanivimab monoclonal antibody monotherapy on hospitalization and mortality among outpatients at high risk of COVID-19 complications. Methods In this observational study we compared outpatients who received bamlanivimab monoclonal antibody from December 9, 2020 to March 3, 2021 to non-treated patients with a p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 14 publications
2
58
0
Order By: Relevance
“…48 studies were identified for full-text review and 40 studies were excluded because they had no comparison groups between Bamlanivimab treatment and control or outcomes were not available. A total of 8 studies [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] comprising of 13573 adult patients with COVID-19, including 4191 in the BAM (administered alone) and 9382 in the control group arm, were included in this meta-analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…48 studies were identified for full-text review and 40 studies were excluded because they had no comparison groups between Bamlanivimab treatment and control or outcomes were not available. A total of 8 studies [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] comprising of 13573 adult patients with COVID-19, including 4191 in the BAM (administered alone) and 9382 in the control group arm, were included in this meta-analysis.…”
Section: Dear Editormentioning
confidence: 99%
“…Real-world data surrounding the use of monoclonal antibody among SOT recipients is sparse. In an observational study comparing outpatients who received bamlanivimab with non-treated patients, bamlanivimab was associated with fewer hospitalizations and mortality within 28 days [ 25 ]. This study included 12 SOT recipients but outcomes were not reported specific to this group.…”
Section: Therapeuticsmentioning
confidence: 99%
“…Physicians review with patients the EUA Fact Sheet for each mAB and explain they could be assigned any of the EUA-governed mABs. 2-4…”
Section: Original Version 10 February 24 2021mentioning
confidence: 99%
“…Neutralizing monoclonal antibodies (mAb) targeting SARS-CoV-2 were granted U.S. Food and Drug Administration (FDA) Emergency Use Authorization (EUA) for treatment of mild to moderate Covid-19, and significantly decrease hospitalization and death in this patient population. [1][2][3][4][5][6][7][8][9] However, clinical use is limited due to lack of access, logistical challenges of administration, and incomplete clinician and patient awareness. 10 The comparative effectiveness of one mAb versus another is also unknown.…”
Section: Introductionmentioning
confidence: 99%